A study of problem solving skills and non-functional attitudes of children who get training for football - Gulsum Bastug; Kursat Acar; Mehibe Akandere (Türk Spor ve Egzersiz Dergisi)
This study aims to research problem solving skills and non-functional attitudes of children who train for football. It involves 120 students, 60 of whom get regular football training and the other 60 of whom do not. The average age of the participants is 12 ± 08 years. To the experimental group and control group applied'the Problem Solving Inventory' (PSI), developed by Heppener and Petersen (1982) and adapted into Turkish by Taylan, Savasir and Sahin (1997), in addition to 'the Non-functional Attitudinal Scale' (NFAS), developed by Weissman and Beck, and adapted into Turkish by Sahin and Sahin (1992). Independent t test was used to establish the difference between the groups. Paired sample t test was used to detect the difference between pre-test and post-test. There is a statistically meaningful difference in problem solving skills between the pre-test and post-test of experimental group (p gt;0.05). There is no statistically meaningful difference between the pre-test and post-test scores regarding problem solving skills of experimental and control groups (p gt;0.05). When the pre-test scores related to non-functional attitudes were compared in terms of experimental and control groups, a statistically meaningful difference was detected between the two groups (p lt;0.05). The problem solving skills of the experimental group increased as a result of football exercises. Furthermore, there is a meaningful difference between pre-test and post-test scores of non-functional attitudes of the experimental group. It was determined that football exercises applied in this study positively affect problem solving skills and non-functional attitude levels of participants.